The analysis of the strain level and the predicted human error probability for critical hospital tasks - Burford, Eva-Maria (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2012)
South African hospitals, as a result of numerous factors, have the problem of an increasing workload for nursing staff, which in turn may affect patient treatment quality. This project aimed at addressing patient treatment quality specifically from the perspective of worker capabilities by investigating the strain level and predicted human error probability associated with specific patient-centered tasks in the South African health care sector. This was achieved through two independent yet interlinked studies which focused on seven patient-centred tasks. The tasks analysed were the tasks of setting up and changing intravenous medication, administering injection and pill medication, measuring blood glucose, temperature and heart rate and blood pressure. In the first study, work environment and task characteristics, task structure and execution were analysed. In addition to the task execution, the resulting strain levels, in the form of heart rate measures and subjective ratings of workload, were studied. The second study determined the error protocols and predictive error probability within the healthcare environment for the seven pre-defined tasks. The results for the first study established that different organizational and environment factors could affect task complexity and workload. The individual task components and information processing requirements for each task was also established. For the strain analysis, significant results for the tasks were determined for heart rate frequency and the heart rate variability measures, but some of these were contradictory. For the second study, specific error protocols and error reporting data were determined for the hospital where this research was conducted. Additionally the predictive error probability for the pre-defined tasks was determined. This combined approach and collective results indicate that strain and predictive error probability as a result of task workload can be determined in the field as well as being able to identify which factors have an effect on task strain and error probability. The value of this research lies in the foundation that the gathered information provides and the numerous potential applications of this data. These applications include providing recommendations aimed at improving nursing work environment with regards to workload, improving patient treatment as a result of a reduction in errors and the potential foundation these results provide for future research
Keywords: Nursing errors -- South Africa -- Prevention; Nursing -- South Africa -- Psychological aspects; Hospitals -- Employees -- Health and hygiene -- South Africa; Nursing -- Job stress -- South Africa